Burden of lower respiratory infections in the Eastern Mediterranean Region between 1990 and 2015: findings from the Global Burden of Disease 2015 study - Moradi-Lakeh, Maziar; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: We used data from the Global Burden of Disease 2015 study (GBD) to calculate the burden of lower respiratory infections (LRIs) in the 22 countries of the Eastern Mediterranean Region (EMR) from 1990 to 2015. - METHODS: We conducted a systematic analysis of mortality and morbidity data for LRI and its specific etiologic factors, including pneumococcus, Haemophilus influenzae type b, Respiratory syncytial virus, and influenza virus. We used modeling methods to estimate incidence, deaths, and disability-adjusted life-years (DALYs). We calculated burden attributable to known risk factors for LRI. - RESULTS: In 2015, LRIs were the fourth-leading cause of DALYs, causing 11,098,243 (95% UI 9,857,095-12,396,566) DALYs and 191,114 (95% UI 170,934-210,705) deaths. The LRI DALY rates were higher than global estimates in 2015. The highest and lowest age-standardized rates of DALYs were observed in Somalia and Lebanon, respectively. Undernutrition in childhood and ambient particulate matter air pollution in the elderly were the main risk factors. - CONCLUSIONS: Our findings call for public health strategies to reduce the level of risk factors in each age group, especially vulnerable child and elderly populations.
GBD 2015 Eastern Mediterranean Region Adolescent Health Collaborators: M. Moradi-Lakeh, J.B. Jonas, A.H. Mokdad [und 141 weitere]
Published online: 3 August 2017
Gesehen am 14.05.2020